An investigation on leading characteristics of rapidkuantan bus passengers using correspondence analysis - Sharifah, Awang (2015)
Kuantan facing huge transformation in their bus transportation system when most of the bus companies discontinue their operations because profitability issue and of the number of bus passengers has declined. The efforts to solve this problem have failed since Kuantan did not have detail information on bus and passengers characteristics. RapidKuantan was introduced in early 2013 and a study needs to be conduct to avoid the same issues. The travel data collected by previous study were not able to describe the leading characteristics of routes covered without the application of more rigours such as correspondence analysis. Researchers often use continuous data analysis (quantitative analysis) to perform the analysis. Some studies can be misleading in determining the correct method of analysing. This study shows how the analysis can be done for categorical travel data (qualitative analysis) using correspondence analysis which is a dimension reduction technique similar to factor analysis but extends factor analysis in handling of categorical data/variables. The leading characteristics for can be identified from correspondence analysis. The questionnaire survey was done for the selected routes in Kuantan and Pekan for one month. The questionnaire form was distributed at the bus stop and on the bus involving 1340 respondents. The study area was divided into four zones and different characteristics were determined for each zone. It can be summarised that the leading characteristics for bus passengers in Zone A (Pekan) were secondary student who from/to home, the bus passenger for Zone B (Gambang) were University student which were from/to shopping with time of return between 11 am to 1 pm, for zone C (Sungai Lembing) the bus passengers were from/to work and business with income less than RM2000 while passengers from zone D (Teluk Cempedak) mostly were from/to school and using bus once a while during weekend. At the end of this study, the strategies to improve bus ridership for each zone were proposed based on Transportation Handbook and Traffic Impact Assessment (TIA) method. This study would like to recommend future research to separate the inbound and outbound passengers when conducting data collection and analysis.